2019
DOI: 10.1037/xhp0000604
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of sustaining attention in a gradual-onset continuous performance task.

Abstract: Continuous performance tasks are frequently associated with a vigilance decrement, particularly when target events are rare and after prolonged time on task. Here we characterized the time course of a performance decrement that happens more rapidly. Using the gradual-onset continuous performance task (the gradCPT), we presented participants with a long sequence of scenes that gradually faded in and out. Participants pressed a button as soon as they detected scenes in one category and ignored scenes in another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 52 publications
(113 reference statements)
3
14
0
Order By: Relevance
“…Previous studies have linked commission errors to a failure to suppress frequent responses (Jun et al, 2019;Wilson et al, 2016). Consistent with this proposal, an analysis on response time (Additional file 1: S6) showed that responses became faster as the experiment progressed.…”
Section: Scene Cptsupporting
confidence: 68%
See 2 more Smart Citations
“…Previous studies have linked commission errors to a failure to suppress frequent responses (Jun et al, 2019;Wilson et al, 2016). Consistent with this proposal, an analysis on response time (Additional file 1: S6) showed that responses became faster as the experiment progressed.…”
Section: Scene Cptsupporting
confidence: 68%
“…Health-related concerns I am worried that I or people I love will get sick from the coronavirus I am worried that the coronavirus will delay the treatment of other illnesses that I or people I love may have (Helton & Russell, 2011;Jun et al, 2019), we computed A' (Grier, 1971;Stainslaw & Todorv, 1999) as a measure of detection sensitivity. Objections can be raised to the use of A' (Verde et al, 2006), so in Additional file 1: S5, we report d' results.…”
Section: Item Category Item Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that, traditionally, the EV decrement has been examined by simple signal detection tasks wherein it is commonly observed a progressive loss in sensitivity: a behavioral pattern explained by the resources overload model as the consequence of a progressive depletion in the available attentional resources (R. A. Grier et al, 2003;Jun, Remington, Koutstaal, & Jiang, 2019;See et al, 1995;Warm et al, 2008). However, as demonstrated by recent research, the loss in sensitivity might be an artifact of simple vigilance tasks wherein it is usually observed a floor rate on FA (Claypoole et al, 2018;Thomson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One potential contributing agent is the tendency of persons with high levels of MM, compared to those with lower levels, to more commonly integrate incidental and irrelevant environmental cues during perception and evaluation (Lopez, Salinger, Heatherton, & Wagner, ). One study showed no association between MM and performance on selective sustained attention (Jun, Remington, Koutstaal, & Jiang, ), and a recent meta‐analysis found no association between MM and distractibility after correcting for small‐study effects (Wiradhany & Nieuwenstein, ). Longitudinal research is needed to discern how MM impacts development of attention over the course of adolescence.…”
Section: Media Multitasking and Adolescent Cognitive Developmentmentioning
confidence: 99%